Hearts of Middlefield : A Man of His Word - Book 1 - Fuller, Kathleen (Nashville, Tenn. : Thomas Nelson, 2009)
When she is abandoned by her husband, pregnant Amish wife Moriah receives a marriage proposal from her husband's twin brother Gabriel, which she accepts despite her fear that he may also betray her.
Keywords: Amish -- Fiction -- Social life and customs; Middlefield (Ohio) -- Fiction; Amish Country (Ohio) -- Fiction; Fiction